2019
DOI: 10.1016/j.heares.2019.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic, perceptual, and cognitive factors underlying musicians’ benefits in noise-degraded speech perception

Abstract: Previous studies have reported better speech-in-noise (SIN) recognition in musicians than nonmusicians while others have failed to observe this "musician SIN advantage." Here, we aimed to clarify equivocal findings and determine the most relevant perceptual and cognitive factors that do and do not account for musicians' benefits in SIN processing. We measured performance in musicians and nonmusicians on a battery of SIN recognition, auditory backward masking (a marker of attention), fluid intelligence (IQ), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 73 publications
4
66
2
Order By: Relevance
“…Our findings parallel Schellenberg (2011) who found that musicianship was associated with IQ and Digit Span (WM and attention). They also converge with studies demonstrating relations between cognition (e.g., WM and auditory attention) and SIN performance in musical individuals (Strait and Kraus, 2011;Sares et al, 2018;Yoo and Bidelman, 2019;but see Escobar et al, 2020). Thus, musicians' cocktail party benefits observed here might result from a refinement in both auditory-perceptual and cognitive abilities, both of which could aid degraded speech-listening skills.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings parallel Schellenberg (2011) who found that musicianship was associated with IQ and Digit Span (WM and attention). They also converge with studies demonstrating relations between cognition (e.g., WM and auditory attention) and SIN performance in musical individuals (Strait and Kraus, 2011;Sares et al, 2018;Yoo and Bidelman, 2019;but see Escobar et al, 2020). Thus, musicians' cocktail party benefits observed here might result from a refinement in both auditory-perceptual and cognitive abilities, both of which could aid degraded speech-listening skills.…”
Section: Discussionsupporting
confidence: 85%
“…Each participant was strongly right-handed (87.0 ± 18.2 laterality index; Oldfield, 1971) and had obtained a collegiate level of education (17.8 ± 1.9 years). Musical training enhances categorical processing and speech-in-noise listening abilities (Bidelman et al, 2014;Yoo and Bidelman, 2019). Consequently, all participants were required to have < 3 years of music training throughout their lifetime (mean years of training: 1.3 ± 1.8 years).…”
Section: Participantsmentioning
confidence: 99%
“…Each participant was strongly right-handed (87.0 ± 18.2% laterality index; Oldfield, 1971) and had obtained a collegiate level of education (17.8 ± 1.9 years). Musical training is known to modulate categorical processing and SIN listening abilities (Parbery-Clark et al, 2009;Bidelman and Krishnan, 2010;Zendel and Alain, 2012;Bidelman et al, 2014;Bidelman and Alain, 2015b;Yoo and Bidelman, 2019). Consequently, we required that all participants had minimal music training throughout their lifetime (mean years of training: 1.3 ± 1.8 years).…”
Section: Participantsmentioning
confidence: 99%